Handling Social Stigma Around Covid-19 Case Study in Lut Tawar District - Abdul Gani; Mappeaty Nyorong; Thomson P Nadapdap (Journal La Medihealtico, 2021)
The aim is to analyze the handling of the social stigma of Covid-19 in terms of social aspects and aspects of government policy, the case study of Lut Tawar District, Central Aceh Regency. The research design used qualitative research with a descriptive approach. There were 7 informants in this study, consisting of 1 head of the covid task force, 1 head of the puskesmas, 1 village head, 3 community leaders who were exposed to covid 19 and 1 community member who was not exposed to covid 19 in Lut Tawar District, Central Aceh. Data analysis techniques with data reduction, data presentation, and drawing conclusions. The results showed that the informants knew the covid 19 virus and its prevention, fear and worry appeared stigma on people who had cough, flu and fever were considered symptoms of covid 19, people stayed away and did not want to be in contact with the informant even though they had recovered. lack of village officials paying attention to communities exposed to covid 19. The government, heads of health centers and village heads have carried out their duties in dealing with stigma in the community by establishing command posts, coordinating patients exposed to health workers, driving vaccination programs, prohibiting people from gathering and making protocol regulations health. The conclusion obtained from the results of this study is that efforts to involve influencers to strengthen messages that can reduce stigma, change patterns of friendship behavior and prevention efforts have been carried out starting from lower levels of government to upper levels.